2018
DOI: 10.4102/sajo.v2i0.31
|View full text |Cite
|
Sign up to set email alerts
|

Breast-conserving therapy for breast carcinoma: Margins, re-excision and recurrence rates

Abstract: IntroductionBreast cancer affects 1 million women in the developed world every year. 1 The burden of breast cancer is also on the rise in the developing world. According to Jones, 2 it is estimated that 70% of new cancer cases will occur in the developing world by the year 2020.Until the 1970s, the Halsted radical mastectomy had been the surgical procedure in the management of breast cancer irrespective of size. It was described and performed by William Stewart Halsted in 1882.3 It included the excision of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“… 3 , 38 This study determined a relative IBTR of 6.5% with a mean time to recurrence time of 34.4 months and is comparable to local and international recurrence rates which are reported as acceptable if between the 5% – 15% range. 1 , 11 , 14 , 16 , 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 , 38 This study determined a relative IBTR of 6.5% with a mean time to recurrence time of 34.4 months and is comparable to local and international recurrence rates which are reported as acceptable if between the 5% – 15% range. 1 , 11 , 14 , 16 , 19 …”
Section: Discussionmentioning
confidence: 99%
“…The recurrence rates post-BCT vary with an acceptable range of 5% – 15%, although some studies have reported higher and lower incidences. 8 , 9 , 10 , 11 , 12 , 13 Local studies performed at Groote Schuur Hospital in Cape Town showed a 5-year recurrence of 6.8% (median follow-up of 60 months) 14 with a smaller study conducted in Johannesburg reporting a 5.5% recurrence (median follow-up of 65 months). 15 Newer studies report significantly lower recurrence rates.…”
Section: Introductionmentioning
confidence: 98%
“…In eight of the 16 studies that reported oncoplastic breast surgery (OPBS) procedures, with a total of 764 patients, latissimus dorsi myocutaneous flap was specified as one of the techniques used, with a total of 112 (15%) patients receiving this procedure. 12,16,18,19,21,32,33 Only one study documented the Wise pattern mastopexy surgery, which was performed on 136 (18%) patients. 15 The level 1 oncoplastic surgery approach was performed on 91 (12%) patients, making it the third most prevalent procedure that was mentioned in the review.…”
Section: Oncoplastic Breast Surgery Techniques Usedmentioning
confidence: 99%